2007
DOI: 10.1128/aem.01085-07
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Transcriptomic Analyses Demonstrate Interactions between the Transcriptional Regulators CtsR and Sigma B inListeria monocytogenes

Abstract: Listeria monocytogenesB positively regulates the transcription of class II stress response genes; CtsR negatively regulates class III stress response genes. To identify interactions between these two stress response systems, we constructed L. monocytogenes ⌬ctsR and ⌬ctsR ⌬sigB strains, as well as a ⌬ctsR strain expressing ctsR in trans under the control of an IPTG (isopropyl-␤-D-thiogalactopyranoside)-inducible promoter. These strains, along with a parent and a ⌬sigB strain, were assayed for motility, heat re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
68
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(77 citation statements)
references
References 69 publications
7
68
1
1
Order By: Relevance
“…To illustrate, an L. monocytogenes ⌬sigB strain had significantly higher hly transcript levels under growth conditions similar to those used in this study (59). In another study (33), the same ⌬sigB strain also showed slightly but significantly higher plcA transcript levels than those in the parent strain when bacteria were exposed to B -inducing conditions (salt stress). The ⌬sigB strain has also been shown to have higher hemolytic activity than 10403S, supporting increased virulence gene expression in the absence of B (10,53).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…To illustrate, an L. monocytogenes ⌬sigB strain had significantly higher hly transcript levels under growth conditions similar to those used in this study (59). In another study (33), the same ⌬sigB strain also showed slightly but significantly higher plcA transcript levels than those in the parent strain when bacteria were exposed to B -inducing conditions (salt stress). The ⌬sigB strain has also been shown to have higher hemolytic activity than 10403S, supporting increased virulence gene expression in the absence of B (10,53).…”
Section: Discussionsupporting
confidence: 61%
“…The P2 prfA promoter region consists of two overlapping promoters, one recognized by A and one recognized by B (53,60,67), indicating a positive regulatory role for B in prfA expression. This positive regulatory role for B initially appeared to be contradicted by observations of increased virulence gene expression and hemolytic activity in a ⌬sigB strain (10,33,53,59). However, in the gram-positive pathogen Staphylococcus aureus, B appears to have both positive and negative roles in regulating expression of virulence factors, positively influencing expression of a number of adhesins and negatively influencing expression of numerous exoenzymes and toxins (3).…”
mentioning
confidence: 99%
“…The first cluster contains five immotile variants showing extreme HHP and heat resistance. Resistance to various stresses, as seen for most variants, might be explained by simultaneous activation through regulatory networks of the different stress mechanisms, as previously described for HrcA, CtsR, and B in L. monocytogenes (10,11). The second cluster contains two stressresistant variants with anaerobic growth and aerobic biofilm formation similar to the wild type (Fig.…”
Section: Discussionsupporting
confidence: 55%
“…In addition, a large number of genes were found to be negatively influenced by B , in particular genes encoding flagellar and ribosomal proteins. Intriguingly, many of the B -dependent effects observed in these studies appear to be indirect, i.e., through secondary gene regulatory systems, such as the stress-related transcriptional regulators HrcA and CtsR, the key virulence regulator PrfA, and the RNA chaperone Hfq (15,16).…”
mentioning
confidence: 96%